2018
DOI: 10.1111/josh.12609
|View full text |Cite
|
Sign up to set email alerts
|

Crime Prevention Through Environmental Design (CPTED) Characteristics Associated With Violence and Safety in Middle Schools

Abstract: The CSA is useful for assessing school environments that are associated with violence-related behaviors and perceptions. The CSA might help guide school environmental modifications to reduce violence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…First, school planners and architects should ensure that security measures are not overly intrusive to the extent that they impinge on the design principles that have been found to enhance academic achievement (Barrett et al, 2015;Tanner, 2009). Second, higher quality school facilities are associated with more positive school climate (Uline & Tschannen-Moran, 2008); and third, novel research suggests that using CPTED to improve facility design might support students' sense of safety, which is associated with psychological comfort, a positive school climate, and a healthy learning environment (Lamoreaux & Sulkowski, 2019;Lindstrom Johnson et al, 2017;Vagi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, school planners and architects should ensure that security measures are not overly intrusive to the extent that they impinge on the design principles that have been found to enhance academic achievement (Barrett et al, 2015;Tanner, 2009). Second, higher quality school facilities are associated with more positive school climate (Uline & Tschannen-Moran, 2008); and third, novel research suggests that using CPTED to improve facility design might support students' sense of safety, which is associated with psychological comfort, a positive school climate, and a healthy learning environment (Lamoreaux & Sulkowski, 2019;Lindstrom Johnson et al, 2017;Vagi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Based on extant research, student perceptions are critical to understanding the hypothesized impact of CPTED on the school climate and academic outcomes. A recent study by Vagi et al () involved assessing the relationship between student perceptions of safety and CPTED by evaluating school facilities’ level of adherence to CPTED principles as well as students’ perceptions of school climate and safety. Over 4,000 students from 50 middle schools participated in this study, which assessed the CPTED principles of natural surveillance, access management, territoriality, physical maintenance, and order maintenance.…”
Section: Cptedmentioning
confidence: 99%
“…In line with this, the research has shown that a decline in SC is related to higher BP at school [30], which include telling lies and breaking rules [31] and externalizing behaviors [3], or even in the increase of absenteeism [27]. Research has shown that inadequate characteristics of the physical environment (e.g., inadequate lighting, hiding places, gang-related or hate-related graffiti, inadequate supervision of corridors, and poor maintenance) can create opportunities for conflict and violence and foster tolerance for aggressive behavior [32]. A meta-analytic review developed by Reaves et al [10] concluded by a significant relationship between students' perceptions dimensions of SC and BP over time.…”
Section: Relationships Between School Climate Behaviour Problems Andmentioning
confidence: 99%
“…Based on an architectural philosophy that aims to prevent criminal or anti-social behavior through the climate, CPTED primarily focused on natural surveillance, access control, and territorial reinforcement [ 35 ], considering four main mechanisms: space design, space use, circulation and circulation patterns, and territorial characteristics and space deterioration. The benefits of CPTED in reducing the incidence of BP and school violence have been largely demonstrated (e.g., [ 32 , 36 ]). When analyzing the associations between the physical attributes of schools and violence-related behaviors, Vagi et al [ 32 ], found an association between better scores on the CPTED and a lesser probability of students missing school due to safety issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation